Amorphous FeNiCu-MOFs as highly efficient electrocatalysts for the oxygen evolution reaction in an alkaline medium. Issue 37 (7th September 2022) - Wu, Hao; Zhai, Qingxi; Ding, Fan; Sun, Dongyue; Ma, Yujie; Ren, Yilun; Wang, Biao; Li, Fengqi; Bian, Haifeng; Yang, Yurong; Chen, Lan; Tang, Shaochun; et al.
Abstract : The preparation of low-cost and high-activity oxygen evolution reaction (OER) catalysts is a technical bottleneck in the field of electrolysis of water to produce hydrogen. Schematic diagram of preparation process and OER process of amorphous FeNiCu-MOF. Abstract : The preparation of low-cost and high-activity oxygen evolution reaction (OER) catalysts is a technical bottleneck in the field of electrolysis of water to produce hydrogen. Amorphous metal–organic frameworks (MOFs) with low-cost transition metals have attracted increasing attention in the catalytic field, yet metal atoms that are the main active sites are still ambiguous. Here, we synthesized a series of amorphous ternary Fe x (NiCu)3− x -MOFs via an ultrasonic method. The optimal amorphous FeNiCu-MOF is found to be able to supply a current density of 10 mA cm −2 merely at a low overpotential of 260 mV with a small Tafel slope of 61 mV dec −1 and exhibits high durability over 24 h. Moreover, density functional theory (DFT) calculations show that the Fe atoms are the main active sites for the OER in the FeNiCu-MOF. This work shows that amorphous ternary MOFs have great potential for application in OER electrocatalysts due to the multiple synergistic effects and amorphous MOF structures.